FROM SPACE FLIGHTS TO OSTEOPOROSIS - Giancarlo Bilancio; Cinzia Lombardi; Massimo Cirillo; Rado Pišot; Jörn Rittweger; Natale G. De Santo (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2015)
Space missions (microgravity) alter the balance between bone formation/resorption and induce bone loss. This effect represents a major limiting step in the realization of long-term space missions. A similar picture is induced by prolonged immobilization at bed (bed rest).  The Osteoporosis and Muscular Atrophy project (OSMA) was a research program sponsored by the Italian Space Agency which included 35-day bed rest experiments in healthy young men. Anthropometric data of these experiments indicated the expected bone mass reduction in some segments of the leg and body weight redistribution from non-fat mass to fat mass. According to the current view, the bone mass reduction due to microgravity/bed rest is associated with the release of calcium from the bone into the bloodstream (hypercalcemia) which, in turn, lowers the secretion of parathyroid hormone and increases urinary calcium excretion. One of the main unsolved points in this view is that hypercalcemia is mild and transient during microgravity/bed rest whereas parathyroid hormone reduction is sustained. The analyses of the OSMA bed-rest will focus on the possible differences between early changes and later changes in indices of calcium homeostasis and bone metabolism during bed rest. The research on the mechanisms underlying bone mass loss during microgravity/ bed rest could be of help not only to space medicine but hopefully also for prevention and control of bone ageing and osteoporosis.